2011
DOI: 10.1111/j.1748-7692.2011.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

The behavioral context of common dolphin (Delphinus sp.) vocalizations

Abstract: Correlations between surface behavior and concurrent underwater vocalizations were modeled for common dolphins (Delphinus spp.) in the Southern California Bight (SCB) over multiple field seasons. Clicks, pulsed calls, and whistles were examined, with a total of 50 call features identified. Call features were used to classify behavior using random forest decision trees, with rates of correct classification reaching 80.6% for fast travel, 84.6% for moderate travel, 59.8% for slow travel, and 58% for foraging beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 65 publications
(79 reference statements)
4
47
0
Order By: Relevance
“…The ob served patterns in common dolphin foraging corre sponded to behavioral patterns of mesopelagic and small pelagic organisms during cool and warm months, respectively. Echolocation activity was predominantly nocturnal, confirming the findings of previous acoustic studies that showed nighttime being an important foraging time for common dolphins (Henderson et al 2012, Wiggins et al 2013. The acoustic record also indicated reduced echolocation activity between April and June, similar to the low regional abun- (2015).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The ob served patterns in common dolphin foraging corre sponded to behavioral patterns of mesopelagic and small pelagic organisms during cool and warm months, respectively. Echolocation activity was predominantly nocturnal, confirming the findings of previous acoustic studies that showed nighttime being an important foraging time for common dolphins (Henderson et al 2012, Wiggins et al 2013. The acoustic record also indicated reduced echolocation activity between April and June, similar to the low regional abun- (2015).…”
Section: Discussionsupporting
confidence: 85%
“…Recent studies in the same region have shown distinct diel behavioral patterns of common dolphins, where foraging mainly occurs at night and travel and social behavior occurs during the day (Henderson et al 2012, Wiggins et al 2013. The observed diving be havior suggests that the dolphins nocturnally feed on mesopelagic organisms which migrate to the epipelagic zone (surface to 200 m depth) at dusk.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, although variation in acoustic parameters can relate to behavioural state (Azevedo et al, 2010;MayCollado, 2013) and may be useful in predicting surface behaviour (Henderson, Hildebrand, & Smith, 2011;Henderson, Hildebrand, Smith, & Falcone, 2012;Hernandez, Solangi, & Kuczaj, 2010) the available information poorly explains the causative factors of this variability. Esch, Sayigh, Blum, et al's (2009) study is the notable exception in detailing the influence of stress on whistle parameters and production rates.…”
mentioning
confidence: 99%
“…Methods in most common use range from t-tests, ANOVA and Chi-square tests or non-parametric equivalents to regression models (Deecke et al 2005, Filatova et al 2009, Foote et al 2004, Lemon et al 2006, Lu铆s et al 2014, Oleson et al 2007, Sjare and Smith 1986, from simple linear models to those incorporating smooth terms, random effects and generalized estimating equations (Quick and Janik 2008, DeRuiter et al 2013, Di Iorio and Clark 2010, Stimpert et al 2015, Visser et al 2016. Other authors use randomization-based methods Solow 2008, Miller et al 2009) or machine-learning classification methods such as random forest decision trees [Henderson et al 2012]. While some authors have suggested the use of state-switching models for animal call rate data (e.g.…”
mentioning
confidence: 99%